Accountability of Account Administration for Confiscated Fund from Criminal Cases: A Perspective of Institutional Isomorphism - Indah Permata Sari; M Nur A Birton; M Adrian Muluk (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to critically analyze the account administration of confiscated funds from criminal cases at the Public Prosecution Service of the Republic of Indonesia using three-dimensional Isomorphism of DiMaggio Powel’s New Institutional Theory. Design/Methodology/Approach: We employ qualitative approach using three-dimensional Isomorphism of DiMaggio Powel’s New Institutional Theory; coercive pressure, mimetic pressure dan normative pressure. We interviewed 21 informants including officials from Special Crimes and General Crimes Section who are responsible for the account administration of confiscated funds. Also, with auditors from the Supreme Audit Institutions who audited the Public Prosecution Service of the Republic of Indonesia, and the Corruption Eradication Commission officials to get new views on how the conduct the account administration of confiscated funds.Research findings: The results indicate that there is coercive pressure in making regulations for account administration of confiscated funds in the form of repeated findings from the Supreme Audit Institutions and the Minister of Finance Regulation of 182/PMK.05/2017. Mimetic pressure is also indicated with the requirement to imitate succeeded similar organizations. The General Attorney's Office has to clarify organizational structure for the Evidence and Confiscation Management Section at the District Attorney's level and establish competency standards for all officials. This means less professionalism due to the absence of procedure supported by information system, which becomes normative pressure.Theoretical contribution/Originality: This study contributes to the literature on exploring public sector phenomena in the perspective of three-dimensional Isomorphism of New Institutional Theory; as well as explaining changes in policy and organization structure for the account administration of confiscated funds from criminal cases.Practitioner/Policy implication: This study provides input to reform the account administration of confiscated funds from criminal cases to make it more accountable on its policies and organization structure.Research limitation/Implication: This study only explains and evaluates the weaknesses of account administration of confiscated funds. There is the need of aspects reconstruction based on three-dimensional Isomorphism of DiMaggio Powel’s New Institutional Theory in order to be accountable on its policies and organization structure.